The Effectiveness of Singing Methods and Demonstration Methods to Improve Understanding of Sexual Education in Early Childhood - Setyarini, Norma; Dewanti, Sri Sularti; Sugiyo Pranoto, Yuli Kurniawati (Journal of Primary Education, 2021)
The occurrence of acts of sexual harassment in early childhood, among others, is due to the lack of sexual education and readiness of schools and parents in conveying sexual education to early childhood. This study aims to analyze the effectiveness of singing methods and demonstration methods on understanding sexual education in early childhood. The design of this study used an experimental method with a pretest-posttest control group design by analyzing quantitative data on the effectiveness of the singing method and the demonstration method on understanding sexual education in early childhood. The research samples were Miftahul Jannah Islamic Kindergarten students as the experimental class and Bunga Harapan Kindergarten as the control class. Data collection used sexual education observation sheets and evaluated using N-gain and Independent T-Test. The findings found that experimental class understanding of early childhood sexual education was more successful than control class. Students' understanding of sex education increased by an average of 0.83 for the high category, while the control class increased by an average of 0.64 with the moderate category. It showed that a singing and demonstration methods can improve early childhood understanding of sexual education